Live Imaging of Adult Neural Stem Cells in Rodents - Ortega, Felipe; Costa, Marcos R. (Frontiers in Neuroscience, 2016)
The generation of cells of the neural lineage within the brain is not restricted to early development. New neurons, oligodendrocytes and astrocytes are produced in the adult brain throughout the entire murine life. However, despite the extensive research performed in the field of adult neurogenesis during the past years, fundamental questions regarding the cell biology of adult neural stem cells (aNSCs) remain to be uncovered. For instance, it is crucial to elucidate whether a single aNSC is capable of differentiating into all three different macroglial cell types in vivo or these distinct progenies constitute entirely separate lineages. Similarly, the cell cycle length, the time and mode of division (symmetric versus asymmetric) that these cells undergo within their lineage progression are interesting questions under current investigation. In this sense, live imaging constitutes a valuable ally in the search of reliable answers to the previous questions. In spite of the current limitations of technology new approaches are being developed and outstanding amount of knowledge is being piled up providing interesting insights in the behavior of aNSCs. Here we will review the state of the art of live imaging as well as the alternative models that currently offer new answers to critical questions